Case Study Analysis Of Marketing Communication Strategies On Tiktok Account @tenuedeattite - Yasmine, Az Zahra Putri; Yuliana, Nina (Jurnal Sosial Sains dan Komunikasi, 2024)
TikTok is an application or social media platform whose growth rate is very fast, currently TikTok users in Indonesia have reached 99.79 million accounts. With a large audience, TikTok is used by online businesses to introduce and market products or services to target markets, one example is the TikTok account @tenuedeattire. The large number of online businesses offering their products or services on the TikTok application has triggered quite tight competition among online businesses in offering their products to consumers. This research aims to analyze marketing communication strategies and what forms of marketing communication strategies are carried out by the TikTok account @tenuedeattire. This research uses qualitative methods by analyzing content in order to explain and understand symbolic messages or messages in various forms and also includes unstructured data. The results of this research state that the marketing communication strategy carried out by the TikTok account @tenuedeattire contains content by using existing features in the TikTok application which aims to build brand awareness, reach a wider target market, increase sales. generate profits at a certain level. This research also produced an explanation of the marketing content concept AIDA (Awereness, Interest, Desire, Action).